2018
DOI: 10.1111/phpp.12402
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of chronic actinic dermatitis in relation to climate changes and air pollution during the past 15 years in Korea

Abstract: The increased incidence of CAD may be related to sun hours and inversely related to PM10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Sun exposure can be one of the most significant risk factors for CAD. Prior studies 6 suggested that sun exposure and outdoor activities are well‐established predisposing factors to CAD. Worldwide, increased opportunity for ultraviolet exposure in summer contributes to higher CAD prevalence and poorer patients' quality of life 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Sun exposure can be one of the most significant risk factors for CAD. Prior studies 6 suggested that sun exposure and outdoor activities are well‐established predisposing factors to CAD. Worldwide, increased opportunity for ultraviolet exposure in summer contributes to higher CAD prevalence and poorer patients' quality of life 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PLE and CAD are the most common photosensitive dermatosis 3,4 . Research showed with the increase in climate change and air pollution, the incidence of PLE and CAD is obviously increasing during the past 15 years in Korea 5 . The observation that PLE and CAD increase in prevalence and severity toward higher northern latitudes, with greater relative differences in UVB between summer and winter, may indicate the importance of UV adaptation 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Generalized erythroderma could also be seen in severe cases. CAD has been reported all over the world, and the incidence of that was thought to be related to sun exposure time (hours) and air quality 2 . Although all races and skin types could be involved, it commonly affects men older than 50‐year‐old who often going outside 3 .…”
Section: Introductionmentioning
confidence: 99%